Pengembangan Video Tutorial Menggambar Desain Rok Secara Digital di Kelas Busana 1 SMK Negeri 2 Tuban - Risa Rifqiyatul Lathifah; Luthfiyah Hidayati (Departement of Mathematics Education, 2023)
Video tutorials are learning media that can help the student learning process because they are easy to use in operation, learning media in the form of video tutorials makes it easier for students to understand teaching material and will consistently affect the level of achievement of student learning outcomes, because learning through video tutorials brings students' interest in learning and play. This study aims: 1. To find out how high the validity level of video tutorials is to draw skirts digitally by validators at SMK Negeri 2 Tuban, 2. To describe learning outcomes using video tutorials to draw skirt designs digitally in Fashion 1 class at SMK Negeri 2 Tuban. The results of the research that has been carried out show that: 1. the development of a video tutorial for digitally drawing skirt designs is feasible to be applied in the fashion class of SMK Negeri 2 Tuban with a total average of 4.07, 2. The test results for class X Fashion Design 1 of SMK Negeri 2 Tuban obtained an average of 78.5% which meets the standard percentage of completeness at 86%.